The Broader Role of Venture Capital Due Diligence - González-Uribe, Juanita; Klingler-Vidra, Robyn; Wang, Su; Yin, Xiang (Review of Financial Studies, 2026)
Abstract Analyzing approximately 2,000 applicants to a U.K. seed fund, this study examines how venture capital (VC) due diligence affects startup outcomes independent of funding decisions. Leveraging random reviewer assignment, we find that due diligence increases 2-year growth but lowers continuation rates among nonfunded applicants, reflecting a dynamic of accelerated scaling or exit. Evidence points to a learning mechanism: due diligence exposes founders to advanced website technologies, prompting capability building in digital skills. Firms selected for due diligence adopt these technologies, even before raising external capital. The findings highlight VC due diligence as a formative process influencing startups beyond the funded few.